Peran Guru Bimbingan dan Konseling mengenai Program dan Layanan BK di SMA - Yulianti Yulianti; Feida Noorlaila Isti’adah; Suci Dwi Lestari; Sabrina Afifah Az Zahra; Melva Sifa Asfiya; Kharisma Nur Fadhillah; Genia Salsabila Septiani Ananta; Anisa Putri Meiliani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
In this interview, we discussed the guidance and counseling program at SMA Negeri 5 Tasikmalaya, with a focus on assessment, academic services, and career guidance. The interview with Mrs. Ana, a guidance counselor at the school, revealed various issues faced by students, such as choosing majors, friendship problems, and learning difficulties. The guidance program at this school aims to help students overcome personal problems, manage stress, and enhance self-learning skills. With the counselor's crucial role in character development, continuous evaluation is necessary to ensure the effectiveness of the services provided. The interview was conducted using an unstructured interview technique with one of the guidance counselors at SMA Negeri 5 Tasikmalaya. The results of the interview found that the performance of guidance counselors at SMA Negeri 5 Tasikmalaya in guidance and counseling programs and services is quite good.